Whenever you're ready : Nora Polley on life as a Stratford Festival stage manager - DeSouza-Coelho, Shawn (Canada : ECW Press, 2018)
"Backstage with one of Canada's greatest stage managers Whenever You're Ready is an intimate account of the career of Nora Polley, who - in her 52 years at the Stratford Festival - has learned from, worked with, and cared for some of the greatest directors, actors, stage managers, and productions in Canadian theatrical history. In so doing, Nora became one of the greatest stage managers this country has ever seen. Here is an account of the Stratford Festival's history like no other. From her childhood forays into a theater her father, Victor, worked tirelessly to help maintain, to her unexpected apprenticeship and the equally unexpected 40 years of stage management it ushered in, this is the Stratford Festival seen exclusively through Nora's eyes. Here is an immersive account of a life spent in service of the theater, told from the ground floor: where actors struggle with lines and anxieties, where directors lose themselves in the work, where the next season is always uncertain, and where Nora - a stage manager, a custodian, a confidante, a pillar, a rock - finds her rhythm, her patience, her perseverance, her love, her consistency, and her invisibility. These are the qualities that make a stage manager great and, whenever you're ready, this book will show you why."--
Includes bibliographical references (pages 379-381) and index.
Keywords: Polley, Nora; Stage management; Stage managers -- Ontario -- Stratford -- Biography